Fast localized single cell membrane poration by bubble-induced jetting flow - Li, Z. G. (2013)
This paper demonstrates a new method to porate single suspension living cell membrane using cavitation bubble-induced high speed jet flow. A microfluidic chip with an array of single cell trapping structures is designed and fabricated to trap sing cell and induce the asymmetric collapse of the cavitation bubble. Myeloma cells suspended in Trypan blue saline solution is tested and single Myeloma cells can be trapped in the trapping structures. The dynamic process is recorded using a high speed camera. This method has great potential in biomedical applications and easy to be integrated to other microfluidic system.